Prevalence and predictors of home and automobile smoking bans and child environmental tobacco smoke exposure: a cross-sectional study of U.S.- and Mexico-born Hispanic women with young children - Kegler Michelle C; Malcoe Lorraine; Gonzales Melissa; Espinoza Judith (BMC, 2006)
Abstract Background Detrimental effects of environmental tobacco smoke (ETS) exposure on child health are well documented. Because young children's primary exposure to ETS occurs in homes and automobiles, voluntary smoking restrictions can substantially reduce exposure. We assessed the prevalence of home and automobile smoking bans among U.S.- and Mexico-born Hispanics in the southwestern United States, and examined the influence of mother's country of birth and smoking practices on voluntary smoking bans and on child ETS exposure. Methods U.S.- and Mexico-born Hispanic mothers of children aged 2 through 12 years were systematically sampled from health clinics in Albuquerque, New Mexico. In-person interviews were conducted with 269 mothers (75.4% response rate) to obtain information on main study outcomes (complete versus no/partial home and automobile smoking bans; child room and automobile ETS exposure) and risk factors (mother's country of birth, maternal and household smoking behaviors). Data were analyzed with chi square tests and logistic regression models. Results Three-fourths (74-77%) of U.S.-born and 90-95% of Mexico-born mothers reported complete automobile and home smoking bans. In multivariate analyses, mother's U.S nativity, mother's current smoking, and presence of other adult smokers in the home were associated with significantly increased odds of not having a complete home or automobile smoking ban. Mother's smoking was associated with child ETS exposure both indoors (odds ratio [OR] = 3.31) and in automobiles (OR = 2.97). Children of U.S.-born mothers had increased odds of exposure to ETS indoors (OR = 3.24; 95% confidence interval [CI]: 1.37-7.69), but not in automobiles. Having complete smoking bans was associated with substantially reduced odds of child ETS exposure both indoors (OR = 0.10; 95% CI: 0.04-0.27) and in automobiles (OR = 0.14; 95% CI: 0.05-0.36). Conclusion This study of Hispanic mothers in the southwestern U.S. indicates that there are substantial differences between U.S.- and Mexico-born mothers in the prevalence of home and automobile smoking bans, and resulting child ETS exposure. Tobacco interventions to increase smoke-free environments for U.S. Hispanic children should focus on both home and automobile smoking practices, especially among U.S.-born mothers, and utilize strategies that impact smoking practices of all household members.